Bioactive nano-scale material approved with HepG2 and MCF-7 cancer cell lines, antimicrobial properties and characterization parameters - Ceylan, Zafer; Inanli, Ayse Gurel; Meral, Raciye; Dalkilic, Semih; Dalkilic, Lutfiye Kadioglu; Karaismailoglu, Mehmet Cengiz; Kose, Nusret (Elsevier, 2024)
The carvacrol nanoemulsion (CNe) was successfully fabricated in the present study. In this regard, the mean particle size (PS) value of the CNe was determined as 321 nm. The zeta potential value of CNe was determined as -54.27 mV while the PDI value of CNe was found as 0.266. With FTIR analysis, the molecular characterization was applied, for example, the peak at 3365 cm(-1) was observed for hydrogen-bonded stretch vibrations of O-H or N-H groups in CNe. The cytotoxic effects of CNe via MCF-7 (88 and 33 % decline in cell viability) and HepG2 (86 and 48 %: decline) were determined. The carvacrol nanoemulsion indicated a high antibacterial effect with 3-9 mu L concentration on the growth of B. cereus with an inhibition zone diameter of 14.3-28.3 mm(-1). The CNe with 0.5-1.5 mL showed bactericidal properties on V. parahaemolyticus with an inhibition zone diameter of 12.6-16.3 mm (p < 0.05). With the novel nano-approach, the carvacrol nanoemulsion with anticancer and antimicrobial properties could play a guiding role for further applications with further studies in industry treatments such as food and hygienic procedures.
Keywords: Bio-nanomaterial; Antimicrobial; Anticancer; Characterization; Industry